Phylogeography and influence of environmental parameters on the invasive shrimp Palaemon macrodactylus and the european native Palaemon longirostris - Petit, Nicolas - Nicolas (2015)
Biological invasions are a major threat of biodiversity. The success of nonindigenousspecies (NIS) can jeopardize native species and modify ecosystemfunctioning, especially in aquatic ecosystems such as estuaries. However, invasionmechanisms such propagule pressure or physiological resistance remain poorly known.The Atlantic commercial delta prawn Palaemon longisrostris, found in estuaries, isfacing the arrival of the oriental shrimp Palaemeon macrodactylus. The objective of thisstudy was to describe the genetic structuring of both species, inferring introductionhistory of the invade and compare both species resistance to environmental stressors. Aphylogeographic approach using the mitochondrial cytochrome oxidase I gene wasconducted on 220 and 142 individuals of P. longirostris and P. macrodactylusrespectively. The former shows a 3-groups genetic structuring in Europe with a patternof isolation by distance. The latter (invasive), we found that two introduction eventslikely occured from Japan (major event) and San Francisco respectively to Europe andother invaded places. Comparative physiological experiments of resistance showed asignificant difference between species of temperature and salinity chronic stresses onthe growth rate. No significant difference was found on the survival of species exposedto a chronic temperature stress but a comparative better resistance of P.longirostris wasobserved for high salinity chronic stress. This study provides first insights into geneticstructure of the native P. longirostris and the invasion history of P. macrodactylus. Italso seems to indicate that better resistance to environmental stress can be find in theinvasive species